Molecular Screening via Sanger Sequencing of the Genetic Variants in Non-Alcoholic Fatty Liver Disease Subjects in the Saudi Population: A Hospital-Based Study - Alsaif, Faisal; Al-hamoudi, Waleed; Alotaiby, Maram; Alsadoon, Amani; Almayouf, Mohammed; Almadany, Hadeel; Abuhaimed, Jawahir; Ghufran, Noman; Merajuddin, Ahmed; Ali Khan, Imran (Metabolites, 2022)
Non-alcoholic fatty liver disease (NAFLD) is one of the most common liver diseases, along with steatosis and non-alcoholic steatohepatitis (NASH), and is associated with cirrhosis and hepatocellular carcinoma. Candidate gene and genome-wide association studies have validated the relationships between NAFLD, NASH, PNPLA3, TM6SF2, and HFE. The present study utilized five polymorphisms in three genes: PNPLA3 (I148M and K434E) TM6SF2 (E167K), and HFE (H63D and C282Y), based on undocumented case–control studies in the Saudi Arabian population. A total of 95 patients with NAFLD and 78 non-NAFLD subjects were recruited. Genomic DNA was isolated, and polymerase chain reaction and Sanger sequencing were performed using specific primers for the I148M, K434E, E167K, H63D, and C282Y. NAFLD subjects were older when compared to controls and showed the significant association (p = 0.0001). Non-significant association was found between gender (p = 0.26). However, both weight and BMI were found to be associated. Hardy–Weinberg equilibrium analysis confirmed that H63D, I148M, and K434E polymorphisms were associated. Genotype analysis showed only K434E variant was associated with NAFLD and non-NAFLD (OR-2.16; 95% CI: 1.08–4.31; p = 0.02). However, other polymorphisms performed with NAFLD and NASH were not associated (p > 0.05), and similar analysis was found when ANOVA was performed (p > 0.05). In conclusion, we confirmed that K434E polymorphism showed a positive association in the Saudi population.